Modeling Emotional Eating through Self-Compassion, Body Dissatisfaction, Emotion Regulation, and Psychological Distress - Pollini, Ornella; Das, Padmini; Maldonado , Cynthia (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: This study aimed to model emotional eating through self-compassion, body dissatisfaction, emotion regulation difficulties, and psychological distress among Canadian adults.Methods and Materials: This cross-sectional correlational study was conducted on 742 adults residing in Canada. Participants were recruited through online advertisements, university mailing lists, community organizations, and social media platforms. Data were collected using the Emotional Eating Scale, Self-Compassion Scale, Body Shape Questionnaire-34, Difficulties in Emotion Regulation Scale, and Depression Anxiety Stress Scales-21. After screening the data for missing values, normality, outliers, and multicollinearity, descriptive statistics, reliability analysis, Pearson correlations, confirmatory factor analysis, and structural equation modeling were performed. Model fit was evaluated using χ²/df, CFI, TLI, IFI, GFI, AGFI, RMSEA, and SRMR. Indirect effects were examined through bias-corrected bootstrapping with 5,000 resamples.Findings: The measurement model demonstrated excellent fit to the data, χ²(392) = 823.47, χ²/df = 2.10, CFI = .965, TLI = .961, IFI = .965, GFI = .929, AGFI = .914, RMSEA = .039, and SRMR = .041. In the structural model, self-compassion negatively predicted emotional eating, emotion regulation difficulties, and psychological distress. Body dissatisfaction positively predicted emotional eating and psychological distress. Emotion regulation difficulties positively predicted both emotional eating and psychological distress, while psychological distress positively predicted emotional eating. Bootstrap analysis confirmed significant indirect effects of self-compassion on emotional eating through emotion regulation difficulties and psychological distress, body dissatisfaction on emotional eating through psychological distress, and emotion regulation difficulties on emotional eating through psychological distress. The model explained 69% of the variance in emotional eating.Conclusion: The findings indicate that emotional eating is shaped by a network of protective and risk-related psychological factors. Higher self-compassion appears to reduce emotional eating directly and indirectly by lowering emotional dysregulation and psychological distress, whereas body dissatisfaction and emotion regulation difficulties increase emotional eating through distress-related pathways. These results highlight the importance of integrated interventions targeting self-compassion, body image, emotion regulation, and psychological distress.